2021
DOI: 10.1128/jvi.00853-21
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Epidemic Diarrhea Virus Inhibits HDAC1 Expression To Facilitate Its Replication via Binding of Its Nucleocapsid Protein to Host Transcription Factor Sp1

Abstract: Porcine epidemic diarrhea virus (PEDV) is an enteric coronavirus causing acute intestinal infection in pigs, with high mortality often seen in neonatal pigs. The newborns rely on innate immune responses against invading pathogens because of lacking adaptive immunity. However, how PEDV disables the innate immunity of newborns towards severe infection remains unknown. We found that PEDV infection led to reduced expression of histone deacetylases (HDACs), especially HDAC1 in porcine IPEC-J2 cells. HDACs are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…Previous studies have reported 11 of the host interacting proteins with PEDV N by other approaches [ 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Among these 11 proteins, only 3 proteins, namely TRIM21, nucleophosmin-1 (NPM1), and poly(A)-binding protein 4 (PABPC4) were confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported 11 of the host interacting proteins with PEDV N by other approaches [ 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Among these 11 proteins, only 3 proteins, namely TRIM21, nucleophosmin-1 (NPM1), and poly(A)-binding protein 4 (PABPC4) were confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite initially serving as a purely structural protein, the nucleocapsid protein of coronavirus is becoming a key regulator of the virusā€“host cellular interface. To date, there have been several reports on the interaction between cellular proteins and the PEDV N protein, as shown by co-immunoprecipitation assays [ 13 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, the broad and accurate interaction profile between PEDV N and cellular proteins still remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus evolved a variety of strategies to promote its persistent infection in the host cell ( Li et al, 2021 ; Su et al, 2021 ; Xu et al, 2021 ). To escape the invasion of the virus, the secretion of antiviral proteins in the host cell was enhanced ( Li et al, 2019 ; Pandey et al, 2019 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al demonstrated that DNAJA3 interacted with the VP1 of the food-and-mouth virus and inhibited viral replication by inducing lysosomal degradation of VP1 and weakening its antagonistic effect in the interferon Ī² signaling pathway [37]. HSP40 has been reported to interact with the 3 end of RNA of the murine hepatitis virus to possibly promote its stability [45]. However, there is a paucity of information on the role of Hsp40 family members in other coronaviruses.…”
Section: Discussionmentioning
confidence: 99%